1999
DOI: 10.1207/s15327914nc340110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 60- and 100-Item NCI-Block Questionnaires With Validation Data

Abstract: Large epidemiological studies often require short food frequency questionnaires (FFQ) to minimize the respondent burden or to control for confounding from dietary factors. In this analysis, we compared the extensively used National Cancer Institute-Block 60- and 100-item FFQs with one another and with usual intake as estimated from 12 days of validation data. The analysis focused on nutrients from different aspects of the diet, including energy, fat, saturated fat, beta-carotene, dietary fiber, and vitamin C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…the long comprehensive questionnaire), showed a reasonable ranking ability to estimate food group intakes. Although no other study has investigated food group intakes, several studies have compared long and short versions of the same questionnaire with regard to nutrients (13)(14)(15) , all of which also showed that both the long questionnaire and the short questionnaire derived from it have reasonable ranking ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the long comprehensive questionnaire), showed a reasonable ranking ability to estimate food group intakes. Although no other study has investigated food group intakes, several studies have compared long and short versions of the same questionnaire with regard to nutrients (13)(14)(15) , all of which also showed that both the long questionnaire and the short questionnaire derived from it have reasonable ranking ability.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, the validity of the DHQ and BDHQ has not been compared. Further, although some studies have compared the validity of the long and short versions of the same questionnaire regarding nutrient intakes (13)(14)(15) , no study has compared these in terms of food group intakes. Such information would aid in the selection of questionnaires that meet the requirements of the particular study design and information needed.…”
mentioning
confidence: 99%
“…Estimates of nutrient intakes from an FFQ are not precise 18,59,60 and there is always the potential for measurement error; however, the FFQ used in our study has been extensively validated in comparison to more extensive methods of measuring dietary intake and biomarkers. 61,62 The 1-year referent period on which exposure data (including dietary intake) was based may not be appropriate to correctly determine associations if dietary intakes over several years is the relevant etiologic time frame. Although we controlled for a wide range of potential confounding demographic, lifestyle and dietary factors there is always the possibility for residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline dietary assessment used in the CTS was an early version of the Block95 FFQ [8,9]. While various versions of this FFQ have been validated in other populations [10][11][12][13], it is critical to describe the reproducibility and validity of this FFQ within the CTS, given the wide range of nutrient-disease investigations being undertaken in this cohort. We also update (with additional follow-up of the cohort) our previously reported results on the association between dietary intake and breast cancer risk among postmenopausal women in the CTS applying the validation results to correct the effect estimates for measurement error [14].…”
Section: Introductionmentioning
confidence: 99%